2018
DOI: 10.1155/2018/6351620
|View full text |Cite
|
Sign up to set email alerts
|

UV Sensitivity of Indium‐Zinc Oxide Nanofibers

Abstract: Indium-zinc oxide (IZO) nanofiber matrices are synthesized on SiO2-covered silicon substrates by the electrospinning method. The nanofibers’ dimensions, morphology, and crystalline structure are characterized by scanning electron microscopy, atomic force microscopy, and X-ray diffraction. The results of studying the electrical properties of nanofibers, as well as their sensitivity to UV radiation depending on the In-to-Zn concentration ratio, are presented. It is shown that the highest sensitivity to UV is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
4

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
2
0
4
Order By: Relevance
“…Besides bulk doped materials, heterostructures of ZnO with M(III) oxides are often obtained. The nanocomposites ZnO/In 2 O 3 have been synthesized with different morphologies and in a wide composition range for the use as gas sensors (Rambu et al, 2011;Singh et al, 2011;Lee et al, 2013Lee et al, , 2017Trakhtenberga et al, 2013;Ma et al, 2016;Espid and Taghipour, 2017;Ilin et al, 2017;Wang et al, 2017;Wei et al, 2017;Zou et al, 2017;Choo et al, 2018;Guo et al, 2018;Liu et al, 2018), humidity sensors (Liang et al, 2012), photocatalysts (Wei et al, 2017;Markova et al, 2018), UV-light detectors (Wang et al, 2009). The studies of gas sensor behavior suggested the increased gas sensitivity of composites, in comparison to pure oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides bulk doped materials, heterostructures of ZnO with M(III) oxides are often obtained. The nanocomposites ZnO/In 2 O 3 have been synthesized with different morphologies and in a wide composition range for the use as gas sensors (Rambu et al, 2011;Singh et al, 2011;Lee et al, 2013Lee et al, , 2017Trakhtenberga et al, 2013;Ma et al, 2016;Espid and Taghipour, 2017;Ilin et al, 2017;Wang et al, 2017;Wei et al, 2017;Zou et al, 2017;Choo et al, 2018;Guo et al, 2018;Liu et al, 2018), humidity sensors (Liang et al, 2012), photocatalysts (Wei et al, 2017;Markova et al, 2018), UV-light detectors (Wang et al, 2009). The studies of gas sensor behavior suggested the increased gas sensitivity of composites, in comparison to pure oxides.…”
Section: Introductionmentioning
confidence: 99%
“…For example, improved sensitivity to butanol and chlorine was found for nanorods and nanoparticles of ZnO modified by In 2 O 3 (3-4 at % indium) (Zou et al, 2017;Liu et al, 2018), while ZnO/In 2 O 3 heterostructures with comparable molar fractions were established for sensing H 2 (Trakhtenberga et al, 2013;Ilin et al, 2017), trimethylamine (Lee et al, 2013) and NO 2 (Espid and Taghipour, 2017). The mechanism of sensitization due to the ZnO/In 2 O 3 heterojunctions is most often speculated based on the electron band energy model at the interface between two oxides proposed in Markova et al (2018). The increase of surface sensitivity to gases is rationalized in terms of potential barrier modification and charged double layer formation within the contact of ZnO/In 2 O 3 phases (Singh et al, 2011;Ma et al, 2016;Wei et al, 2017;Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ранее нами было показано [5], что нанонити IZO благодаря своей высокой чувствительности являются перспективным материалом для разработки УФ-сенсоров. В настоящей работе экспериментально исследована кинетика нарастания и спада тока нанонитей IZO при включении и выключении источника УФ и представлен анализ этих экспериментов на основе численного моделирования.…”
unclassified
“…Синтез нанонитей IZO проводился методом электроспиннинга, который является одной из разновидностей золь-гель-метода и подробно описан в нашей работе [5]. Нанонити наносились на подложку Si−SiO 2 в виде спутанных волокон (рис.…”
unclassified
See 1 more Smart Citation